Changes in the self-determination and cultural and social life of the Croatian, Slovenian and Serbian nationalities in Hungary until 2019 in the light of the legislative changes - Bali, Lóránt (Közép-Európai Közlemények, 2024)
The aim of the study is to show how the socio-economic conditions of the Slovenes, Croats and Serbs have evolved over the last thirty years. In the thirty-year period after the regime change, the system of relations of self-determination of nationalities has undergone continuous change and development. The study also deals in depth with the nationality policy of state-socialist Hungary. Without this background, it would not be possible to evaluate the first thirty years correctly. The self-organization and cultural life of the nationalities under study is significantly influenced by the fact that the majority of them live in rural areas in underdeveloped regions of the country. The cultural elite of each nationality was late in coming into being or had to completely reorganise itself after state socialism. In this study, I focus primarily on legislative changes and local elections. I also present the specificities of national cultural civil society organisations.